Tindakan Operasi Plastik Pada Hidung Ditinjau Dari Perspektif Etika Kristen - Modiana Frella Souhally; Ferry Simanjuntak; Yanto Paulus Hermanto (Jurnal Ledalero, 2022)
Abstract: Plastic surgery to change the shape of the nose (rhynoplasty) is a controversy that is present today as knowledge increases in the field of medical technology, increasing aesthetic influence which presents new trends in influencing a person's shape and appearance. On the other hand, nose reconstruction (septoplasty) is also needed because of an accident, disease or certain conditions in the nose. This paper analyzes the issue of plastic surgery on the nose as an effort to provide an understanding of biblical ethics to place this phenomenon in accordance with Christian ethical principles. The goal is for God's people to consider biblical and ethical principles in making ethical decisions before undergoing plastic surgery. In this study, researchers used descriptive analysis methods and literature studies. The type of data used is in the form of various books and articles according to the theme of the discussion. Based on existing research, researchers found that nose specialist plastic surgery procedures must be carried out according to the conditions that occur and are supported by clear goals and motivation. Such as plastic surgery of the cetoplasty type which is mandatory for the method of healing the respiratory tract in the nose and plastic surgery of the rhinoplasty type which actually does not have to be done because it is contrary to God's will, and does not agree with the perspective of bioethics and Christian ethics. It is possible to do this surgical procedure, but it must be based on clear reasons and objectives, and supported by the unavailability of other options apart from how necessary this operation must be carried out.Key words: Plastic Surgery, Septoplasty, Rhinoplasty, Christian Ethics